Job Demand, Hardiness, and Coping Skills as Predictors of General Health among Academic Staff in Public Universities in Ogun State Nigeria - Ogunsanwo, Mojisola A. (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The world over, the importance of the human dimension to organizational sustainability and survival cannot be overemphasized. It is on this premise that this study investigated the combined and relative predictive capacity of job demand, hardiness and coping styles on general health of academic staff in Ogun State, Nigeria. The study adopted a descriptive survey research design of an ex-post facto type. Two research hypotheses were formulated and tested at 0.05 level of significance. Data were collected using a four validated instruments. The instruments were administered to three hundred (300) academic staff randomly selected from the three (3) public universities in Ogun State, Nigeria. Data were analysed using Multiple Regression statistical methods. The findings of this study revealed that job demand, hardiness and coping skills accounted for 26.7% of the variance in the academic staff general health (R = .517; R 2 = .267; Adj. R 2 = .267; F (2, 298) = 21.057; p = .000). Also, the study revealed that job demand (Î² = .128; t = 4.009; p = .000), coping skills (Î² = .111; t = 2.917; p = .000) and hardiness (Î² = .107; t = 2.008; p = .000). In conclusion, this study enhances our understanding of the contributive power of job demand, hardiness and coping skills on employees' general health. Through this study it is hoped that organizations and individual employee will become more aware of how job demand, hardiness and coping skills can affect employees' general health in different situations. It is therefore recommended that a organizations should always look for ways to improve the occupational health of their employees. Keywords: Job Demand, Hardiness and Coping Styles on General Health of Academic Staff